Tanzania Economic Update, November 2017 : Managing Water Wisely - World Bank Group (World Bank, Washington, DC, 2017)
The tenth edition of the Tanzania Economic Update covers the state of the economy and includes a near term outlook, with a special focus chapter on one of the most cross-cutting determinants of development outcomes, water resource management. Part One presents a discussion and analysis of Tanzania's recent macroeconomic and fiscal performance, with an updated outlook for the near term. Part Two presents an analysis of Tanzania's management of its water resources, showing that the management of these resources has massive implications for Tanzania's people, its economy and its environment, and that there is an urgent need for improvements.